Representations of Young Cancer Survivorship: A Discourse Analysis of Online Presentations of Self. Issue 1 (January 2019) - Lewis, Peter; Weston, Kathryn M.
Abstract : Background: More young people are surviving treatment for cancer than ever before. Survival can have an adverse impact on their transition to adulthood. Discourses of cancer are applied to cancer survivors of all ages, but they manifest differently for young people. Objective: The aim of this study was to describe practices of self-representation in an online Web site that supports young Australian cancer survivors. Method: We conducted a discourse analysis of images and text produced by young cancer survivors (aged 18–35 years) on a public cancer charity Web site. Results: The dominant subject position of participants published on this web site is one of empowered, beautiful cancer survivor. This applies to young people who have learned to embrace their cancer as providing a positive influence on their lives. However, this discourse can marginalize those whose cancer experience remains a source of distress or shame. Conclusion: Web based media can provide a valuable forum for some young people to celebrate their cancer survival and to affirm the constructive influence that their cancer experience has had on their lives. However, we ponder the apparent unsuitability of some forums for young cancer survivors who have not yet found cause for celebration. Implications for Practice: Nurses have the opportunity to contribute to the development of supportive structures that meet the specific needs of different groups of young cancer survivors. This might mean assisting young cancer survivors who are struggling to find meaning in their cancer experience to negotiate the establishment of a new normal that they can embrace.